2013
DOI: 10.1080/07350015.2013.801776
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Marginal Law of a Time Series With Applications to Heavy-Tailed Distributions

Abstract: In the absence of precise information on the dynamics of a stationary time series, a natural estimator for a parametric marginal distribution is obtained by maximization of the "quasi marginal" likelihood, which is a likelihood written as if the observations were independent. We study the effect of the (neglected) dynamics on the asymptotic behavior of this estimator. The consistency and asymptotic normality of the estimator are established under mild assumptions on the dependence structure. Applications of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 44 publications
0
10
0
1
Order By: Relevance
“…Similar models have been successfully adopted in different application fields, and seem to be particularly attractive in economics and finance (Menn and Rachev, 2005;Rachev et al, 2011;Francq and Zakoian, 2013;Babaei et al, 2015). The main applied contribution of our work is to show that the model that we propose is able to capture most of the basic features observed in international trade data.…”
Section: Introductionmentioning
confidence: 89%
“…Similar models have been successfully adopted in different application fields, and seem to be particularly attractive in economics and finance (Menn and Rachev, 2005;Rachev et al, 2011;Francq and Zakoian, 2013;Babaei et al, 2015). The main applied contribution of our work is to show that the model that we propose is able to capture most of the basic features observed in international trade data.…”
Section: Introductionmentioning
confidence: 89%
“…The data in this study demonstrates dependence, but this does not remove the necessity for one to consider the heavy tailed features present in the data, nor diminish the importance of a study on heavy tailed marginal distributions and ways in which these features are a crucial contribution to dynamical models of LOB volume profiles. The study of heavy tails in a marginal context is critical, as this has important effects on the accuracy of the estimators (Francq and Zakoian 2013). Studies that consider heavy tailed features in financial market data include and are not limited to: Cont (2001); Francq and Zakoian (2013).…”
Section: 34mentioning
confidence: 99%
“…Koedijk and Kool (1992) studied the exchange rate returns for three East European currencies and found that their tail indices are smaller than 2. Francq and Zakoïan (2013) investigated nine major financial markets in the world and argued that the time series modelling driven by a heavy-tailed noise may be more appropriate to financial data analysis; see Rachev (2003) and She and Ling (2020), among many others. All previous evidences show that there is a practical and urgent need to study the heavy-tailed time series.…”
Section: Introductionmentioning
confidence: 99%